Integration of metabolomics and transcriptomics unravels the identification of TPS gene family and functional characterization of a sesquiterpenoid synthesis gene in Curcuma kwangsiensis - Ming, Ruhong; Xie, Xin; Ling, Wei; Wei, Yuping; Chen, Jianhua; Yao, Shaochang; Tan, Yong; Li, Liangbo; Huang, Rongshao; Huang, Ding; Xiao, Jian (Frontiers in Plant Science, 2025)
IntroductionCurcuma kwangsiensis S.G. Lee et C.F. Liang, a member of the Zingiberaceae family, is abundant in sesquiterpenes. However, the sesquiterpene metabolome of C. kwangsiensis remains poorly characterized, and its terpene synthase (TPS) gene family has not yet been identified.MethodsIn this study, metabolomics analysis was employed to systematically profile the metabolites in different tissues of C. kwangsiensis and identify differential expressed metabolites. Transcriptome sequencing technology was utilized to analyze the different expressed genes (DEGs), providing insights into the molecular basis of its secondary metabolism.ResultsThe experimental results demonstrated that a total of 177 terpenoids were upregulated in the rhizome, while 175 terpenoids showed upregulation in the tuber. KEGG classification revealed that nine differential metabolites were identified in the Sesquiterpenoid and Triterpenoid Biosynthesis pathway, of which eight were sesquiterpenes. By employing bioinformatics approaches to identify the TPS gene family in C. kwangsiensis, a total of 24 TPS gene family members were identified. One candidate gene CkTPS10 was cloned, heterologously expressed in Saccharomyces cerevisiae, and functionally characterized. The catalytic products, α-copaene and farnesol, of the enzyme were consistent with the results of key differential metabolite screening, indicating that the CkTPS10 play a pivotal role in the biosynthesis of sesquiterpene components in C. kwangsiensis.Conclusion and DiscussionIntegrated transcriptomic and metabolomic analysis represents an efficient approach for investigating the secondary metabolites of C. kwangsiensis, offering a theoretical foundation for deciphering the biosynthetic pathway of sesquiterpene compounds in this plant.